2022
DOI: 10.1007/s00330-022-09180-w
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian imaging radiomics quality score assessment: an EuSoMII radiomics auditing group initiative

Abstract: Objective To evaluate the methodological rigor of radiomics-based studies using noninvasive imaging in ovarian setting. Methods Multiple medical literature archives (PubMed, Web of Science, and Scopus) were searched to retrieve original studies focused on computed tomography (CT), magnetic resonance imaging (MRI), ultrasound (US), or positron emission tomography (PET) radiomics for ovarian disorders’ assessment. Two researchers in consensus evaluated each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For instance, a review of cholangiocarcinoma encompassing 38 original studies reported a median RQS of 9, amounting to just 25.0% of the total RQS ( 52 ). Similarly, a review focusing on ovarian imaging, which included 63 studies, found a median RQS of 6, corresponding to 30.6% of the total RQS, indicating lower scoring ( 53 ). Another meta-analysis covering 57 ovarian cancer studies reported an average RQS of 30.7%, which is also considered unsatisfactory ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a review of cholangiocarcinoma encompassing 38 original studies reported a median RQS of 9, amounting to just 25.0% of the total RQS ( 52 ). Similarly, a review focusing on ovarian imaging, which included 63 studies, found a median RQS of 6, corresponding to 30.6% of the total RQS, indicating lower scoring ( 53 ). Another meta-analysis covering 57 ovarian cancer studies reported an average RQS of 30.7%, which is also considered unsatisfactory ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inter-reader variability and reproducibility of the radiomics features are crucial for the validation of the radiomics model, and they are often missing in current studies. A recent systematic review pointed out that the methodological rigor and quality of radiomics studies are still unsatisfactory in ovarian pathologies, with a reported radiomics quality score of 6, corresponding to 16.7% of the total score, which is lower compared with other fields of research in radiomics studies [169][170][171].…”
Section: Mrimentioning
confidence: 99%
“…In recent years, extensive studies using radiomics methods based on CT and MRI have linked quantitative image features to diagnosis, response evaluation, and prognostic prediction in patients with OC [ 8 , 17 , 18 ]. Nevertheless, it has remained difficult to assess the clinical value of radiomics in OC owing to the complexity of the methods and varying study designs.…”
Section: Introductionmentioning
confidence: 99%